NOTES ON MALAYSIAN CYPERACEAE-II * - KERN, J. H. (REINWARDTIA, 1954)
Since 1884 the name Cyperus zollingeri Steud. has been misapplied to a common tropical species, the correct name of which is C. tenuieulrnis Boeck.It appears that C.rubroviridis Chermez.(1919) and C. ramosiiKiikenth.(1925) are synonymous with C. zollingeri Steud. (1855).Cyperus leucoeephalus Retz, and C. pulehellus R. Br. are treated as specifically distinct.The Philippine record of C.leucoeephalus is referred to C. pulehellus.A tentative arrangement of the Malaysian material of the polymorphous Cyperus sanguinolentus Vahl is given.Mariscus maritimus Miq. is reduced to Cyperus dubius Rottb.,C. pulcherrimus f. retiglwmis Valck. Sur. to the species.The previous Malaysian records of Cyperus stenostachyus Benth.and C. polystachyos 1. longispiculatus Valck. Sur. are erroneous. A survey of the distribution of some Malaysian species is given.The following new combinations are made: Cyperus trialatus (Boeck.) Kern; C. sanguinolentus ssp. melanocephahis (Miq.) Kern, ssp.cyrtostachys (Miq.) Kern, and ssp. teijsmannii (Miq.) Kern.